2021
DOI: 10.3389/fvets.2021.611076
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain and Delivery of Antimicrobial Drugs in Smallholder Livestock Production Systems in Uganda

Abstract: This study assessed the veterinary drug supply chain in Uganda, the constraints faced by the actors, and how the challenges influence the use of antimicrobial (AMs) by livestock farmers. We carried out stakeholder consultation workshops, key informant interviews and a knowledge, practices, and awareness survey with actors of the veterinary drug supply chain. We also profiled drugs stored in 23 urban and peri-urban drug shops in Lira and Mukono districts to record the commonly sold drugs. The veterinary drug su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 15 publications
6
25
0
Order By: Relevance
“…This present study and our earlier study also alluded to the supply chain issue related to medicines where only a limited range of antimicrobials was available for use ( 16 ). The findings are consistent with those reported by Dione et al ( 55 ) in Uganda where supply chain constrains were identified as potential drivers of inappropriate AMU ( 55 ). Therefore, we suggest a critical review of the procurement processes so that an informed forecast and procurement of veterinary medicines, including antimicrobials can take place to ensure a sustainable supply of veterinary medicines in the Fijian veterinary clinics.…”
Section: Discussionsupporting
confidence: 92%
“…This present study and our earlier study also alluded to the supply chain issue related to medicines where only a limited range of antimicrobials was available for use ( 16 ). The findings are consistent with those reported by Dione et al ( 55 ) in Uganda where supply chain constrains were identified as potential drivers of inappropriate AMU ( 55 ). Therefore, we suggest a critical review of the procurement processes so that an informed forecast and procurement of veterinary medicines, including antimicrobials can take place to ensure a sustainable supply of veterinary medicines in the Fijian veterinary clinics.…”
Section: Discussionsupporting
confidence: 92%
“…Imprudent use of antimicrobials resulting from self-prescribing with under and overuse have been reported in developing countries ( 6 , 11 ). Our results also suggest that incomplete courses of antimicrobials took place due to the high costs of the antimicrobials; thus, farmers used antimicrobial sub-therapeutically and saved the rest for future use, which have been similarly reported in other studies ( 18 , 48 , 49 ).…”
Section: Discussionsupporting
confidence: 85%
“…Our results demonstrated that farmers self-prescribed antibiotics and did not complete the full course of antibiotics. The treatment decisions were based on their past experience instead of on the advice of the veterinary professionals, a practice similarly reported in other studies ( 48 ). Imprudent use of antimicrobials resulting from self-prescribing with under and overuse have been reported in developing countries ( 6 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Without a correct diagnosis, there is an obvious risk of inappropriate antibiotic use, which in this regard increases the risk of AMR development in both districts, independently of the access to animal health services. It has previously been shown that, due to the lack of laboratory services, animal health service personnel in these districts often recommend broad-spectrum antibiotics like oxytetracycline to farmers [ 35 ], which are known to be prone to induce resistance [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as in many other countries antibiotics can constitute an important source of income for veterinarians, one should therefore be aware that there might be economic incentives for veterinary practitioners to recommend antibiotic treatment to farmers, increasing the risk for over- and misuse [ 38 ]. Regarding the income for veterinarians from sales of pharmaceuticals, Dione et al [ 35 ] found antibiotics to be the most profitable drug category in both Lira and Mukono. Favorably, from an AMR perspective, the proportions of farmers that used veterinary drugs in response to disease problems without prior consultation from a professional animal health worker were low in both districts.…”
Section: Discussionmentioning
confidence: 99%